Plant Pathology in India: Vision 2030 - IPS, Secretary (Indian Phytopathology, 2011)
In this book, a vision for the future of plant pathology has been described that must be pursued and supported for sustainable production of healthy plants upon which life itself depends. Â The Indian Phytopathological Society (IPS) recognizes the need to look to the future to best position the discipline to meet future societal needs and scientific opportunities.